Geographical information systems database of cultural heritage resources of Osogbo and their tourism potential - Titilayo O Olukole (African Journal of Hospitality, Tourism and Leisure, 2014)

(untitled)
This paper uses the Geographical Information Systems (GIS) to create a database of the cultural heritage resources of Osogbo such that the cultural information of this heritage sites can be archived and retrieved thereby showcasing their tourism potentials. Osogbo, an ancient Yoruba town, now the capital of Osun State, plays an important role in the history of the Yoruba race, hence the need to preserve her cultural heritage using advancements in technology such as the GIS and Global Positioning Systems (GPS). The spatial locations of the major cultural resources of the area were obtained using a Garmin® Global Positioning Systems (GPS). ArcView GIS software was used in developing cartographic representation of the spatial locations of the cultural resources and then linked to the respective attribute data. This produced a database for archiving, analyzing and displaying the cultural tourism resources of Genesis Art Gallery, Nike Art Gallery, Susan Wenger’s Art Gallery, First Palace of Ataoja and National Museum, Osogbo. Such documentation and digital presentation as this intends to highlight Osogbo’s cultural heritage and develop her tourism potentials. The outcome of this study is expected to attract more tourists to the area while providing tourism destination managers and planners with an important preliminary tool needed for further development.